2017
DOI: 10.5902/2316980x27343
|View full text |Cite
|
Sign up to set email alerts
|

Fertilização mineral e calagem no crescimento de mudas de <em> Eucalyptus camaldulensis

Abstract: Resumo: A utilização de substratos pode garantir mudas com características morfológicas adequadas para o plantio no campo. Diante disso, realizou-se experimento em viveiro com o objetivo de avaliar a influência da utilização de calcário e diferentes formulações de adubos na produção de mudas de Eucalyptus camaldulensis. As mudas da espécie foram produzidas em tubetes com capacidade para 160 cm³, oriundas de sementes que foram colocadas para germinar em areia e vermiculita. Ao atingirem 15 cm de altura, as plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In a study conducted by Rodrigues et al (2016), the application of limestone promoted an increase in eucalyptus diameter, with greater increments in this dendrometric attribute than in vertical growth, similarly to the present study, which also showed greater increments in diameter than in height. In turn, Vieira & Weber (2017) FLORESTA, Curitiba, PR, v. 50, n. 4, p. 1788PR, v. 50, n. 4, p. -1797 obtained improvements in the soil chemical attributes after limestone application, which provided an increment in height, diameter, and biomass of E. camaldulensis seedlings. Rodrigues et al (2016) observed an increase in height, up to 1.50 m, on E. urophylla x E. grandis clonal plants cultivated in Cerrado, at 18 months after the addition of limestone, on the surface or incorporated.…”
Section: Height Diameter and Estimated Volumementioning
confidence: 94%
See 1 more Smart Citation
“…In a study conducted by Rodrigues et al (2016), the application of limestone promoted an increase in eucalyptus diameter, with greater increments in this dendrometric attribute than in vertical growth, similarly to the present study, which also showed greater increments in diameter than in height. In turn, Vieira & Weber (2017) FLORESTA, Curitiba, PR, v. 50, n. 4, p. 1788PR, v. 50, n. 4, p. -1797 obtained improvements in the soil chemical attributes after limestone application, which provided an increment in height, diameter, and biomass of E. camaldulensis seedlings. Rodrigues et al (2016) observed an increase in height, up to 1.50 m, on E. urophylla x E. grandis clonal plants cultivated in Cerrado, at 18 months after the addition of limestone, on the surface or incorporated.…”
Section: Height Diameter and Estimated Volumementioning
confidence: 94%
“…The Eucalyptus, due to its high adaptability to climatic conditions and different soils, is considered as tolerant to acidity and low soil fertility, and as non-responsive to any soil correction (CQFS, 2016). However, several studies indicate an increase in productivity when using fertilizers and soil acidity correctives (CASTRO FARIA et al, 2015;WEBER, 2017;RODRIGUES et al, 2016;MAEDA et al, 2015;GUIMARÃES et al, 2015). Because of the high costs of applying these products, even at the beginning of the production process, and the scarcity of resources, the administration of doses below the necessary may occur, resulting in low crop yields.…”
Section: Introductionmentioning
confidence: 99%